Increasing education awareness for students in developing learning motivation in Tongging village, sub-district Merek, Karo district, North Sumatera province - Ginting, Herli; Maghfirah, Awan; Sianturi, Herty Afrina (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2019)
Community empowerment that was raised was to provide counseling about the importance of an education in Karo District, Brand District of Tongging Village. Education is a learning, knowledge, and skills acquired in both formal and non-formal schools. Education is very important for every human being because it can create quality human beings, intellectual, and far from ignorance. The state has regulated the right of every Indonesian citizen to get education as a means to improve his quality of life, namely the Article 28 C of paragraph 1 and 2 and article 31 paragraph 1 and 2. With a pulakita education, we can build the nation to be more advanced. In Tongging village, there are 3 schools namely Pelita PAUD, 044854 Public Elementary School and Karya Tongging Private Middle School. The number of students is also still low, namely 36 PAUD students, 162 SD students and 45 SMP students. The problem at this school is the lack of facilities in schools such as inadequate bathrooms and the lack of electricity. But despite the inadequate facilities of children and adolescents in Tongging have never been affected by juvenile delinquency which has an impact on social irregularities.